Mapping and verification of grain shape QTLs based on an advanced backcross population in rice - Xia, Duo (PLoS One, 2017)
Grain shape is a key factor that influences both the appearance quality and grain yield of rice. To clarify the genetic basis of grain shape, an advanced backcross population was developed from the cross of a slender indica variety Jin23B and a round japonica variety QingGuAi, and a total of 10 quantitative trait loci (QTLs) for grain shape were detected over 2 years. Three QTLs, qGW1, qGS3 and qGS7 have large effects on grain shape and were detected in both years. To further validate their effects, the BC(4)F(2) populations of the three QTLs were constructed. The alleles from QingGuAi of qGW1 and qGS7 both greatly increase grain width and the alleles from Jin23B of qGS3 greatly increase grain length. The allele variations of the three QTLs lead to the totally different grain shape of the two rice varieties. Our study provides insights into the genetic bases of grain shape and will promote the improvements of grain quality and yield in rice.